1997
DOI: 10.1121/1.418236
|View full text |Cite
|
Sign up to set email alerts
|

A spark-generated bubble model with semi-empirical mass transport

Abstract: This paper describes the time evolution of bubbles generated by underwater electrical discharges. The oscillations of these high-temperature vapor and plasma bubbles generate acoustic signatures similar to the signatures generated by air guns, underwater explosions, and combustible sources. A set of model equations is developed that allows the time evolution of the bubble generated by a spark discharge to be calculated numerically from a given power input. The acoustic signatures produced by the model were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Schaefer's results showed that the larger the P H , the smaller the bubble maximum radius and the higher the peak frequency [23]. Jeffrey conducted a theoretical study revealing that the bubble period and the minimum rarefaction pressure were dependent on P H , while the first peak pressures of WSW were unrelated to P H when P H < 0.9 MPa [24]. Based on Jeffrey's results, Lu presented a new model including bound-bound transitions in the calculation of the thermal radiation power [25].…”
Section: Introductionmentioning
confidence: 99%
“…Schaefer's results showed that the larger the P H , the smaller the bubble maximum radius and the higher the peak frequency [23]. Jeffrey conducted a theoretical study revealing that the bubble period and the minimum rarefaction pressure were dependent on P H , while the first peak pressures of WSW were unrelated to P H when P H < 0.9 MPa [24]. Based on Jeffrey's results, Lu presented a new model including bound-bound transitions in the calculation of the thermal radiation power [25].…”
Section: Introductionmentioning
confidence: 99%
“…Spark generators have been used for studying bubbles in a liquid for quite a long time [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. DYNAFLOW, INC. has several test chambers that can be used to simulate full-scale bubble dynamics, and is equipped with flow diagnostics tools including high speed photography and pressure measurement capabilities.…”
Section: -Experimental Set-upmentioning
confidence: 99%
“…The channel transforms into a cavity filled with a gas which continues to expand even after the internal pressure becomes lower than the external hydrostatic pressure, P<P 0 , due to inertia of the surrounding water flow. A rarefaction pressure pulse is radiated in this stage of the bubble development [1].…”
Section: Introductionmentioning
confidence: 99%